Writing Letters Training in Lumbung Baca Luwungragi Village - Kurniawan, Prasetyo Yuli (Universitas Pancasakti Tegal, 2022)
Community service activity is training in writing correspondence on contextual or real life. The team carried out the movement in the Lumbung Baca village of Luwungragi district of Bulakamba Brebes. The first part is the trainee's initial understanding of correspondence in a contextual approach, then the second part trainee's final experience and skills in writing the letter. This initial understanding is using questionnaires given to trainees. Then the trainees responded to the question to the questionnaire. The questionnaire contains about the knowledge of writing correspondence in contextual or real life. The understanding consists of definitions, objectives, functions, classifications, forms, and types of everyday letters. The student of Universitas Muhadi Setiabudi can show trainee in the following table. Thus, correspondence writing training in a real-life context can explain the trainees writing letters in Luwungragi village. In addition to learning, trainees also gain skills in writing letters for the results of writing a letter because of the devotion report attachment.